Allele frequency database for GlobalFiler™ STR loci in Australian and New Zealand populations. (May 2017) - Taylor, Duncan; Bright, Jo-Anne; McGovern, Catherine; Neville, Sharon; Grover, Denise
Abstract: We assign autosomal allele proportions for Caucasian, Asian, self-declared Aboriginal and pure Aboriginal populations from Australia and Caucasian and Eastern and Western Polynesian populations from New Zealand. Population sample sizes vary from 122 to 528. All populations underwent tests for the presence of allelic dependencies (i.e. departures from the expectations of Hardy Weinberg and Linkage equilibrium) and some large dependencies were observed in the Australian Aboriginal populations. We provide allele frequency files for all populations examined.